Scales and instruments to measure depression in primary care - Lima, Alejandra; Galán Cuevas, Sergio (Mexican Journal of Medical Research ICSA, 2021)
Background: Depression is a public health problem due to the negative impact it generates in the physical, psychological, social and economic areas of the person suffering from it. It is a disorder that is underdiagnosed within the first level of care and to detect it requires brief, valid and reliable instruments that allow health personnel to perform a screening that facilitates early diagnosis and timely treatment. Method: In this systematized review study, scales and instruments were selected that can be applied by health personnel at the first level of care. The selection was made in the Bank of Instruments and Methodologies in Mental Health CIBERSAM and the Inventory of Psychosocial Scales in Mexico 1984-2005. Subsequently, in the databases of Scielo, Redalyc and PUBMED, adaptations and validations were sought for the Spanish-speaking population and the Mexican population. The keywords were used for the search: name of the scale or instrument, validation, psychometric properties, adaptation and Mexican population. Results: Eight scales and instruments were included that meet the necessary characteristics to be used in the first level of care, which aim to assess the level of depression or identify the presence and frequency of depressive symptoms and have adequate psychometric properties in their adaptations and validations for Spanish-speaking population and/or Mexican population. Conclusions: The vast majority of scales and instruments favour health personnel so that they can make a timely diagnosis of depressive disorder. The choice of which is the best for the evaluation will depend on the experience of the health professional in the diagnosis and management of depression.